Pengaruh Kesesuaian Harga dan Ulasan Produk Terhadap Keputusan Pembelian di E-Commerce Shopee - Fachri Makmura; Kartika Sukmawati (Digital Bisnis: Jurnal Publikasi Ilmu Manajemen dan E-Commerce, 2024)
The research entitled "The Influence of Price Match and Product Reviews on Purchasing Decisions in Shopee E-Commerce" aims to determine the partial influence of price and product reviews on purchasing decisions in Shopee e-commerce, as well as knowing the simultaneous influence of price and product reviews on purchasing decisions on Shopee e-commerce. The analytical method in this research uses quantitative primary data with the test stages carried out including: validity test, reliability test, normality test, multicollinearity test, heteroscedasticity test, multiple linear regression test, T test (partial test), F test (simultaneous), and determination test. The data used in this research used a questionnaire instrument and valid data collected from 100 respondents. The sampling method in this research was non-probability sampling with a purposive sampling technique. The testing tool used is IBM SPSS Statistics. The results of the research show that the price variable has a partial or partial effect on purchasing decisions, the product review variable has a partial or partial effect on purchasing decisions, and the price and product review variables have a simultaneous effect on purchasing decisions in Shopee e-commerce.